THE EFFECT OF LEADERSHIP, ORGANIZATIONAL CULTURE, AND EMPLOYEE COMPETENCIES ON THE QUALITY OF FIRE FIGHTING SERVICES AT THE FIRE AND RESCUE SUB-DEPARTMENT OFFICE OF CENTRAL JAKARTA ADMINISTRATION CITY - Hidayat, Ahmad; Mu’allim, Agus; Tuswoyo; Zaini, Zaman; Badruddin, Syamsiah; Pandoyo (CENTRAL ASIA AND THE CAUCASUS, 2022)
The study analyzes the influence of leadership, organizational culture, and employee competence on the quality of fire fighting services at the Fire and Rescue Sub-Department Office (The Office) of Central Jakarta Administration City. The research method is descriptive quantitative that is done using SPSS sav. Data are obtained through questionnaires to respondents from 348 people (population) with a sampling of 87 people. Stages of analysis consist of a) analysis of the frequency distribution of respondents' answers, b) test requirements analysis, and c) test the research hypothesis, which consists of simple and multiple regression analysis, partial and simultaneous t-test with F-test, and analysis of the coefficient of determination. The study shows the relationship of leadership and service quality is 0.295, organizational culture and service quality 0.375, and competence and service quality0.085. The relationship between leadership, corporate culture, and competence, jointly, are moderate on service quality at 0.450. Finally, the percentage of leadership, organizational culture, and competence variables explaining service quality is 17.4%, and others outside the model influence 82.6%.